A single-centre experience rolling out an antibiotic stewardship intervention prior to and during the SARS-CoV-2 pandemic 2019-2022 - Zahra Kassamali Escobar; Todd Bouchard; Cameron Buck; Kamaldeep Sandhu; Chloe Bryson-Cahn (BioExcel Publishing Ltd, 2023)
Background: Antibiotics are prescribed to nearly onehalf of patients with viral respiratory tract infections (RTI) in outpatient settings. This use is ineffective and may cause undue harm and excess cost from unnecessary antibiotic exposure. We implemented a multifaceted intervention to address inappropriate antibiotic prescribing for viral RTI. Here, we discuss the impact over 4 years, before and during the SARS-CoV-2 pandemic. Methods: This observational study describes the implementation and initial impact of a multimodal stewardship intervention on inappropriate antibiotic prescribing for viral RTIs in outpatient care settings at a single centre. We tracked the rate of visits for viral RTI as well as antibiotic prescribing for viral RTIs in urgent care, primary care and the emergency department between January 2018 and March 2022. Data were collected 1 year prior to implementation and 3 years after implementation. The primary outcome - the rate of inappropriate antibiotics prescribed for viral RTIs - was described by calendar year (CY) to review changes after the stewardship intervention. Results: In CY2018, the year prior to implementation of targeted RTI antimicrobial stewardship, the rate of inappropriate RTI antibiotics prescribed was 10% in urgent care, 11% in primary care and 18% in the emergency department (ED). During the first CY of the intervention, rates were 8% in urgent care, 10% in primary care and 16% in the ED. In CY2020, the second year of the intervention, inappropriate RTI antibiotics were prescribed in 5% of urgent care and 3% primary care RTI visits and 15% of ED RTI visits. These rates were similar in CY2021 and the first 3 months of CY2022. Over 30,000 visits for RTIs were seen annually in CY2018 and CY2019. Annual RTI visits dropped to 20,222 in CY2020 and 14,172 in CY2021. Conclusion: Although total visits for non-COVID RTIs decreased by approximately 50% during the first 2 years of the SARS-CoV-2 pandemic, an antimicrobial stewardship intervention was associated with decreases in inappropriate antibiotic prescribing for RTIs. This was maintained throughout 2 years of the pandemic. This article is part of the Antibiotic stewardship Special Issue: https://www.drugsincontext.com/special_issues/antimicrobial-stewardship-a-focus-on-the-need-for-moderation